The Effect of Women Executive on Bank Performance (Study on Banking Firms Listed in Indonesia Stock Exchange in The Period Of 2010 – 2019) - Cassania Dela Pena; Suherman; Sholatia Dalimunthe (LPPM Universitas Negeri Jakarta, 2021)
The aim of this study is to determine the effect of Women Executive on the bank performance of banking firms listed in Indonesia Stock Exchange period of 2010- 2019. Independent variables used in this study is women executive which is measured with female CEO. Dependent variable used in this study is bank performance which is measured with Return on Asset (ROA) and Return on Equity (ROE). This study also uses control variables including board of commissioner size, the proportion of foreign commissioner, the proportion of independent commissioner, firm size, firm growth, dividend policy, firm age, Net Performing Loan (NPL), and Loan to Deposit Ratio (LDR). The data used in this study is taken from annual report of banking firms that are listed in Indonesia Stock Exchange during 2010-2019. The sampling method of this study is purposive sampling. The research model used is unbalanced panel data with Random Effect Model approach. The results obtained from this research is female CEO has significant effect on ROE, but does not have significant effect on ROA.